2016
DOI: 10.21522/tijph.2013.04.04.art059
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Psychosocial Effects of Almajiri system on Child’s Development in Gwange Ward Maiduguri, Borno State, Nigeria

Abstract: Children are known to be the source of joy in every family especially when the parents can afford their basic needs. Children in the northern part of Nigeria are prone to deprivation through almajiri system of education mainly due to respect for misunderstood religious concept and culture among other causes. This study of psycho-social effects of almajiri system on child's development was conducted in Gwange ward, Maiduguri, is aimed at identifying the psychological effects of almajiri system on child's develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Albeit, every child, including Almajiri have rights such as the right to education, health, care, love, adequate food and shelter, live in proper environment; the Almajiri suffers (Chukwu et al, 2016;Mohammed et al, 2022). In almost every street, corner, junction, Almajiri are seen as nearly homeless, poor, neglected, and maltreated child wandering and begging for alms and food because the society, parents, government, have abandoned the real cause of Almajiri education in northern Nigeria (Zakir et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit, every child, including Almajiri have rights such as the right to education, health, care, love, adequate food and shelter, live in proper environment; the Almajiri suffers (Chukwu et al, 2016;Mohammed et al, 2022). In almost every street, corner, junction, Almajiri are seen as nearly homeless, poor, neglected, and maltreated child wandering and begging for alms and food because the society, parents, government, have abandoned the real cause of Almajiri education in northern Nigeria (Zakir et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Parable, psychoactive use among Almajiri in the Northern Nigeria has long been observed in Almajiri students denoting a high prevalence use of different drugs by the students (Abdulmalik et al, 2009). An investigation of psychological effects of Almajiri education system in Borno state, Nigeria reiterated that the children are socially and psychologically inflicted because they lack enough care, stay alone, improper feeding, lack of security, and dangerous experience among other (Chukwu et al, 2016). In Zaria city, Northwestern Nigeria an investigation on psychiatric disorders among Almajiri students was done, and it was found that Almajiri students show more psychiatric problems than the pupils drawn from public primary schools in the area (Abdullateef et al, 2017).…”
Section: Introductionmentioning
confidence: 99%